Society and High Skills: contributions and prospects - Thais Aline Casseb da Silva; Dayhammy Fabrizi Sampaio Paixão (Universidade Federal de Santa Maria (UFSM), 2010)
The intention of this research is to investigate and understand the importance of investing in high-skilled individual and how the family influences that context. For this, we seek the concepts of intelligence and high ability / giftedness to determine the characteristics of this individual and also to demonstrate through a literature and society and the family influence the behavior of a gifted person.